2013
DOI: 10.1063/1.4825178
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of binary nonadditive hard sphere fluid mixture confined in random porous media

Abstract: I analyze the fluid-fluid phase separation of nonadditive hard sphere fluid mixture absorbed in random porous media. An equation of state is derived by using the perturbation theory to this complex system with quenched disorders. The results of this theory are in good agreement with those obtained from semi-grand canonical ensemble Monte Carlo simulations. The contact value of the fluid-fluid radial distribution functions of the reference which is the key point of the perturbation process is derived as well, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The preferential-adsorption-based separation using porous materials is proposed to be an efficient and energy saving method for ethanol-water separation [5,11]. It has been observed that liquids which are miscible in bulk can be phase segregated when confined at nanoscale [12][13][14]. The preferential attraction by the surface of confining nanopore or the size selective penetration through tunable pore for one of the species of the mixture can lead to their phase separation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The preferential-adsorption-based separation using porous materials is proposed to be an efficient and energy saving method for ethanol-water separation [5,11]. It has been observed that liquids which are miscible in bulk can be phase segregated when confined at nanoscale [12][13][14]. The preferential attraction by the surface of confining nanopore or the size selective penetration through tunable pore for one of the species of the mixture can lead to their phase separation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the properties of ethanol–water at interfaces on the molecular level is very important for many chemical and physical processes. It has been proved by many studies that surface-directed phase separation appears in confined binary mixtures while one component is preferentially attracted to the walls. However, with regard to the interaction of ethanol–water mixtures with silica surfaces, our atomistic understanding is far from satisfactory. Water molecules can interact with the surface through hydrophobic or hydrophilic interactions and hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%